Aktivitas Komunikasi Antara Perawat Dan Pasien Penyalahgunaan Narkoba Din Layanan Rehabilitasi Rawat Jalan - Mufti fauzi Rahman Mufti; Ira Hasianna Rambe; Dedeh Dahliah; Siti Nur’aeni; Gaizka verrel Santosa; Sephia Indah Lutpiah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2022)
Backgroun: Doctors, nurses or health care providers are of course closely related to words or language. both simple and complex words sometimes become obstacles in therapeutic communication. Mulyana pointed out how simple words can be interpreted differently, that the meaning of the words conveyed is often ambiguous. Meanings or words are culturally bound. Situational factors, such as the context of place and time and the mood of the communicator, also influence how others interpret the message. Purpose: To explain the communication activities of nurses and patients in drug abuse with outpatient rehabilitation services. Methods: This study uses a constructivist paradigm, data obtained from participant observation, in-depth interviews, and literature study. This study uses qualitative research methods, because what will be studied is a central symptom. Furthermore, this study uses the ethnographic method of communication. Data were obtained from participant observation results, in-depth interview results, and literature study. Results: The results of the study show that the communicative situation that occurs between nurses and drug patients at the Antapani Medika Clinic is normal. In an informal setting, crowded at certain hours. Nurses and patients both carry out their roles. The communicative events that occurred between nurses and drug patients at the Antapani Medika Clinic ran smoothly, between nurses and patients being open to each other, honestly interacting with each other and providing responses. Communicative action between nurses and drug patients takes place using verbal and non-verbal communication. Conclusion: The form of verbal communication from nurses is with requests, statements, warnings to open questions before the patient enters the room for examination by the doctor. The language used tends to be a mixture of Indonesian and Sundanese. Pendahuluan: Dokter, perawat atau penyedia layanan kesehatan tentunya erat kaitan dengan kata-kata atau bahasa. baik kata-kata yang sederhana maupun yang rumit kadang menjadi kendala dalam komunikasi terapeutik. Mulyana mengemukakan betapa kata-kata sederhana bisa diartikan berbeda, bahwa arti kata-kata yang disampaikan, seringkali ambigu. Makna atau kata-kata itu terikat budaya. Factor situasional seperti konteks tempat dan waktu serta suasana hati komunikator, juga memengaruhi cara orang lain menafsirkan pesannya. Tujuan: Untuk menjelaskan aktivitas komunikasi perawat dan pasien dalam penyalahgunaan narkoba dengan layanan rehabilitasi rawat jalan. Metode: Penelitian ini menggunakan paradigma konstruktivis, data diperoleh dari hasil observasi partisipan, hasil wawancara mendalam, dan studi pustaka. Penelitian ini menggunakan metode penelitian kualitatif, sebab yang akan dikaji, merupakan gejala sentral. Selanjutnya penelitian ini menggunakan metode etnografi komunikasi. Data diperoleh dari hasil observasi partisipan, hasil wawancara mendalam, dan studi pustaka. Hasil: Dari hasil penelitian menunjukan bahwa situasi komunikatif yang terjadi antara perawat dan pasien napza di Klinik Medika Antapani normal. Dalam suasana informal, ramai di jam-jam tertentu. Perawat dan pasien sama-sama menjalanakan perannya. Peristiwa komunikatif yang terjadi antara perawat dan pasien napza di Klinik Medika Antapani berjalan secara lancar, antara perawat dan pasien saling terbuka, Jujur saling berinterkasi dan memberikan respon. Tindak komunikatif anatar perawat dan pasien napza berlangsung menggunakan komunikasi verbal dan non-verbal. Simpulan: Bentuk komunikasi verbal dari perawat adalah dengan permintaan, pernyataan, peringatan hingga pertanyaan terbuka sebelum pasien memasuki ruangan pemeriksaan oleh dokter. Bahasa yang digunakan cenderung campuran bahasa Indonesia dengan Sunda.